Western civilization : a brief history, fifth edition -. Volume 2, from the 1400s - Perry, Marvin ([S.l.] : Cengage Learning, 2004)
Western Civilization: A Brief History emphasizes the history of ideas presented within a political chronology. Perry's distinctive writing style and unique approach make this abridged version of Western Civilization: Ideas, Politics & Society an engaging text for the Western civilization survey course. The Fifth Edition includes coverage of recent events and provides students with the pedagogical tools to analyze and interpret events in context. Chapter introductions and chronologies allow students to easily identify important themes, while review questions serve to reinforce knowledge and aid in exam preparation.